INOVASI PENGEMBANGAN SISTEM DIGITALISASI INFORMASI, PENGENDALIAN DAN PELAPORAN LAYANAN PENDIDIKAN MENENGAH KABUPATEN KULON PROGO - Suharyanto; Kisupriyoko (STKIP Subang, 2023)
The facilitation of educational services must be supported by a system and workforce capable of quickly adapting to developments in science and technology. Education services must be able to coordinate and communicate government programs for education services in schools. Schools need accuracy and conformity in secondary education services according to the Special Region of Yogyakarta education strategic plan. In this secondary education service, researchers see an opportunity to conduct research and development. This Research and Development aims to: make an Information Digitization System application, Control and Report on Secondary Education Services, Outreach to schools about the development of Educational service applications and practice the use of the Secondary Education Service Digitization System application in at least 2 (two) schools. The method used in this research is the Research and Development (R&D) method. This method is a method used to produce certain products and test the effectiveness of a product. Utilization of the application technology for the Digitalisasi Layanan Pendidikan Menengah (Si DILA DIKMEN) for school financial accountability using the Research And Development (R&D) method helps school financial managers to be accountable for financial realization to the Center for Secondary Education to be more effective and efficient. The results of this research and development are in the form of the Si DILA DIKMEN application, and trials have been carried out using the application involving 2 schools, and research products have been disseminated to 19 schools, both high school and vocational schools in Kulon Progo. From the results of the pilot implementation of the Si DILA DIKMEN Application, it is known that all schools can operate the application properly.